Resilience and return-to-work pain interventions: systematic review. (21st March 2019) - Wainwright, E; Wainwright, D; Coghill, N; Walsh, J; Perry, R
Abstract: Background: Resilience is a developing concept in relation to pain, but has not yet been reviewed in return-to-work (RTW) contexts. Aims: To explore the role of resilience enhancement in promoting work participation for chronic pain sufferers, by reviewing the effectiveness of existing interventions. Methods: Resilience was operationalized as: self-efficacy, active coping, positive affect, positive growth, positive reinforcement, optimism, purpose in life and acceptance. Five databases were searched for randomized controlled trials (RCTs) whose interventions included an element of resilience designed to help RTW/staying at work for chronic pain sufferers. Study appraisal comprised the Cochrane risk of bias (RoB) tool and additional quality assessment. Findings were synthesized narratively and between-group differences of outcomes were reported. Heterogeneous PICO (population, intervention, comparator, outcome) elements precluded meta-analysis. Results: Thirty-four papers from 24 RCTs were included. Interventions varied; most were multidisciplinary, combining behavioural, physical and psychological pain management and vocational rehabilitation. Four found RTW/staying at work improved with intensive multidisciplinary interventions compared with less intensive, or no, treatment. Of these, one had low RoB; three scored poorly on allocation concealment and selective outcome reporting. Four trials had mixed results, e.g. interventions enabling reduced sick leave for people on short-term not long-term leave; 16 showed no improvement. Five trials reported resilience outcomes were improved by interventions but these were not always trials in which RTW improved. Conclusions: Effectiveness of resilience interventions for chronic pain sufferers on RTW is uncertain and not as helpful as anticipated. Further agreement on its conceptualization and terminology and that of RTW is needed.